Epigenetic repression of E-cadherin by human papillomavirus 16 E7 protein - Laurson, Joanna (Oxford University Press, 2010)
A common feature shared between several human cancer-associated viruses, such as Epstein-Barr virus, Hepatitis B virus and Hepatitis C virus, and Human papillomavirus (HPV) is the ability to reduce the expression of cellular E-cadherin. Since E-cadherin is used by Langerhans cells to move through the stratified epithelium, its reduction may affect the efficiency by which the immune system responds to HPV infection and the length of persistent HPV infections. We observed that the E7 protein of this virus (HPV16) is most efficient at reducing E-cadherin levels. This E7 activity is independent of retinoblastoma protein or AP-2α degradation. Instead it is associated with augmentation of cellular DNA methyltransferase I (Dnmt1) activity. Significantly, inhibition of Dnmt activity re-established E-cadherin levels of the cells, presenting the possibility that similar epigenetic intervention clinically may be a way to re-establish the influx of Langerhans cells into infected epithelium to counteract HPV persistence.